2015
DOI: 10.1016/j.actbio.2014.09.033
|View full text |Cite
|
Sign up to set email alerts
|

A versatile bioink for three-dimensional printing of cellular scaffolds based on thermally and photo-triggered tandem gelation

Abstract: Layer-by-layer bioprinting is a logical choice for the fabrication of stratified tissues like articular cartilage. Printing of viable organ replacements, however, is dependent on bioinks with appropriate rheological and cytocompatible properties. In cartilage engineering, photocrosslinkable glycosaminoglycan-based hydrogels are chondrogenic, but alone have generally poor printing properties. By blending the thermoresponsive polymer poly(N-isopropylacrylamide) grafted hyaluronan (HA-pNIPAAM) with methacrylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
187
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(194 citation statements)
references
References 49 publications
0
187
0
Order By: Relevance
“…11 TRGs have many biomedical applications 12 including drug delivery [13][14][15][16][17][18][19][20][21] and tissue engineering as in-situ forming gels [22][23][24][25][26][27] and in 3-D bioprinting. [28][29][30][31] Furthermore with the increasing recent interest in 3-D printable materials and the need to control the rheology of the solution while printing 32, 33 the areas of potential usage of TRGs has increased since 3-D printing is applied to the manufacture of materials in various industries besides the medical industry, like aerospace, automotive, building and construction, marine, food industry and in manufacturing electronic and optical devices. [34][35][36] In TRGs applications it is highly important to be able to control the gelation point, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…11 TRGs have many biomedical applications 12 including drug delivery [13][14][15][16][17][18][19][20][21] and tissue engineering as in-situ forming gels [22][23][24][25][26][27] and in 3-D bioprinting. [28][29][30][31] Furthermore with the increasing recent interest in 3-D printable materials and the need to control the rheology of the solution while printing 32, 33 the areas of potential usage of TRGs has increased since 3-D printing is applied to the manufacture of materials in various industries besides the medical industry, like aerospace, automotive, building and construction, marine, food industry and in manufacturing electronic and optical devices. [34][35][36] In TRGs applications it is highly important to be able to control the gelation point, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This complex architecture of AC cannot be mimicked simply by encapsulating cells in hydrogels and/or seeding cells onto pre-formed polymeric scaffolds. Such methods do not allow for precise cell-suspension and orientation at the targeted location [120].…”
Section: Future Directionsmentioning
confidence: 99%
“…These studies also demonstrated the possibility to determine and to reduce the shear stresses transmitted to the cells through experimental and numerical studies [17,19,30,46,127]. To address the unique requirements of extrusion bioprinting regarding the print fidelity and biological characteristics, research efforts have been focused on the development of bioinks exhibiting appropriate rheological, mechanical and biological properties [28,32,74,82,100,152,169,174]. A multitude of crosslinking mechanisms, including thermal gelation, ionic and photocrosslinking, have also been explored to induce the in situ gelation of printed materials with the ultimate goal of improving the mechanical properties, the shape fidelity and the formation of interconnected 3D pores throughout the construct [4,28,107], which still remains a major challenge.…”
Section: Extrusion Bioprintingmentioning
confidence: 99%